The Effectiveness of “Improvement of Driver-Behavior Program” on Self-Control of Individuals Whose Driving Licenses Have Been Seized due to Drinking and Driving. - Ýbrahim Taymur; Veli Duyan; Kadir Özdel; Ersin Budak; Buket Belkýz Güngör (Bilişsel Davranışçı Psikoterapi ve Araştırmalar Dergisi)
Objective: The aim of the current study to evaluate the effectiveness of “Improvement of Driver-Behavior Program” on Self-Control of individuals whose driving licenses have been seized for two years due to drinking and driving. Methods: Study sample consisted of 60 volunteers whose driving licenses have been seized for two years due to getting stopped for drunk driving for the second time and who were participated in improvement of driver-behavior program. Self-Control Scale was administered to the group before, at the 6’th week and after the 12-week program. Results: When we examined the Self-Control Scale (SCL) scores; means were 51±17.69. 6 at the first assessment, 54.23±15.61 at the 6’th week, and 48.86±17.76 at the 12’th of the program. Therefore, the alteration in Self-Control Scale Scores during the program was statistically not significant ( F=1,434; p=0.236).Further pair-wise comparison revealed that only the difference between the SCL scores at 6’th and 12’th weeks was statistically significant (p:0,005).Besides, ANCOVA analysis revealed that the age had significant effect on the difference between the SCL scores at the 6’th and 12’th weeks (F=3,858; p:0.027). Conclusion: We conclude that the quality of “Driver-Behavior Improvement Program” should be enhanced by extending the duration of the education and addressing the age factor in improving self-control features of the relevant individuals. [JCBPR 2014; 3(3.000): 182-190]